Regional and local variability in the morphometric traits of two emblematic seagrass species (Zostera marina and Zostera noltei) along the French coast - Lacoste, Élise; Boyé, Aurélien; Blanchet-Aurigny, Aline; Desroy, Nicolas; Auby, Isabelle; Bajjouk, Touria; Bourdier, Constance; Cimiterra, Nicolas; Cordier, Céline; Curd, Amélia; Derrien, Lauriane; Foucault, Élodie; et al. (Peer Community Journal, 2025)

(untitled)
Zostera marina and Zostera noltei are two foundation species that play a crucial role in the functioning of coastal ecosystems. They occur in a wide range of environmental conditions over a large geographical area in the northern hemisphere. The aim of this study was to investigate the scales of variability in the dynamics of these two species in relation to environmental conditions in four sites along the French coasts. We used community trajectory analysis, a multivariate statistical approach that allows quantitative measures and comparisons of ecosystem temporal trajectories. The results show an effect of site position and tidal regime on the seasonal dynamics of the two species. Populations from the southernmost microtidal site showed a seasonal stability in their morphometric traits and a good resistance to present-day climatic conditions. In the meso- and macrotidal regime sites, hydrodynamic conditions and light have led to very different ecological strategies. On the one hand, high tidal currents increased shoot density and root biomass, while on the other hand, low light and less current favoured the development of long leaves to optimise photosynthesis. Finally, variations in meadow development was also observed at the local scale, which requires further investigation to identify the specific drivers. Our discussion suggests that special attention should be paid to interpreting the dynamics of these species according to the scale of observation, and that this diversity of variation scales should be taken into account in conservation measures. In a global context of seagrass bed decline, our study suggests some avenues of research to improve our understanding of seagrass species ecology in order to properly assess the state of coastal waters.